Chiral, sequence-definable foldamer-derived macrocycles. Issue 47 (24th November 2021) - Warnock, Toyah M. C.; Rajkumar, Sundaram; Fitzpatrick, Matthew P.; Serpell, Christopher J.; Dingwall, Paul; Knipe, Peter C.
Abstract : Dipole-controlled pre-organization enables the cyclization of sequence-defined foldamers into macrocycles. The structure and properties of trimeric and tetrameric macrocycles are explored, and their ability to bind cationic guests is demonstrated. Abstract : Nature's oligomeric macromolecules have been a long-standing source of inspiration for chemists producing foldamers. Natural systems are frequently conformationally stabilised by macrocyclisation, yet this approach has been rarely adopted in the field of foldamer chemistry. Here we present a new class of chiral cyclic trimers and tetramers formed by macrocyclisation of open-chain foldamer precursors. Symmetrical products are obtained via a [2 + 2] self-assembly approach, while full sequence control is demonstrated through linear synthesis and cyclisation of an unsymmetrical trimer. Structural characterisation is achieved through a combined X-ray and DFT approach, which indicates the tetramers adopt a near-planar conformation, while the trimers adopt a shallow bowl-like shape. Finally, a proof-of-concept experiment is conducted to demonstrate the macrocycles' capacity for cation binding.